(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Cold Bituminous Emulsion Mixtures have many environmental, logistical, and economic advantages over conventional Hot Mix Asphalt. Nevertheless, their inferior performance and high water sensitivity at early life attract little attentions. Moreover, it is impossible to apply CBEM as a structural surface layer if left without treatment or enhancement. The main aim of this study is to enhance the properties of CBEM for the hope of using it as a structural layer. Thus, a trial has been made to improve CBEM mechanical and durability properties by replacing the Ordinary Portland Cement by the Conventional Mineral Filler with 3 percentages; namely, 0, 50%, and 100%. CBEM mixtures mechanical properties were evaluated in term of Marshall Stability and Flow, Indirect Tensile Strength, and Wheel Track Test. While Moisture damage was evaluated in terms of Retained Marshall Stability. Test results showed that the addition of 100%OPC filler can improve CBEM mechanical and durability properties efficiently. In terms of mechanical properties results, CBEM comprised 100%OPC, can be used as a structural Surface layer based on local Iraqi specifications limits, where mixture enhanced about 1.9, 1.78, 9,4.85, and 2.6 times in term of MS, MF, rutting deformation resistance, resistance to tensile cracking, and moisture damage resistance, respectively as compared to untreated CBEM. Also, CBEM-100%OPC mix seemed comparable (and sometime superior) to HMA, e.g., resistance to rutting of CBEM is about 6.2 times higher than that of HMA. It’s worth to say that OPC upgrades CBEM to a significant level that enables it to use as a structural layer in terms of the mechanical and the durability properties.